Dissemination of Weak Waves in Granular Materials Under Short-Term Impulse Loads; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Bobriakov A. P.; Kosykh V. P.; Revuzhenko A. F.; Kazantsev A. A. Anton Aleksandrovich; Ivushkina N. V. Nataliya Vladimirovna (2016, 2016)
Title screen